THE INFLUENCE OF GOOGLE SITES ON IPAS LEARNING ON SELF REGULATED THROUGH STUDENT LEARNING MOTIVATION - Megasari, Nia; Sri Hariani, Lilik; Ifana Sari, Yuli (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to examine the impact of utilizing Google Sites on students’ self-regulated learning (SRL) abilities within Integrated Natural and Social Sciences (IPAS) instruction, with learning motivation acting as a mediating variable. The research is grounded in the urgent need for educational transformation toward interactive, technology driven learning that cultivates learner autonomy in the context of 21st century education. Employing a quantitative descriptive approach through a case study design, the research involved 100 upper-grade students from SDN Jrebeng Kulon 1, Probolinggo City. Data were gathered using structured questionnaires and analyzed using path analysis to determine both direct and indirect effects among the studied variables. Findings reveal that the integration of Google Sites exerts a positive and statistically significant influence on students’ self-regulated learning, with an R Square value of 0.289, indicating that 28.9% of the variance in SRL is jointly explained by Google Sites usage and learning motivation. Moreover, learning motivation functions as a mediating factor that strengthens this relationship. These results align with Zimmerman’s (2023) Self Regulated Learning Theory and Deci & Ryan’s (2000) Self-Determination Theory, which emphasize autonomy, competence, and social relatedness. Theoretically, the study reinforces the pedagogical potential of digital technology integration in stimulating cognitive, affective, and metacognitive domains. Practically, it recommends that educators employ Google Sites not merely as a content delivery platform but as a transformative medium to cultivate adaptive, technology-based learner autonomy.